ANALISIS DAMPAK ALOKASI ANGGARAN DESA DAN INFRASTRUKTUR DESA PADA TINGKAT KEMISKINAN DI KABUPATEN SEMARANG - Nugraheni, Rahayu Sapta; Ananda, Candra Fajri; Syafitri, Wildan (Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Although the level of poverty in Indonesia, especially in Semarang Regency has decreased significantly, there are two tendencies to be a concern. Since 2014 village budgets have been granted to villages with significant increases to finance rural development. However, it has not shown any real results. This study aims to analyze the aspects that affect the level of village poverty in Semarang Regency. The aspect is basic infrastructure consisting of market access, health access and educational access, population, village original revenue, transfer revenue (village fund, village fund allocation and tax revenue and local retribution share) and allocation of village expenditure consisting of village development expenditure, community development expenditure and community empowerment expenditure. The result of the study shows that the aspects researched are significantly influence the level of village poverty in Semarang Regency. Aspects that affect the level of poverty indicated by the Wald test results are health access, population, Village Original Revenue, allocation of development expenditure, allocation of community empowerment expenditure. Quadrant analysis result shows the comparison between Poverty Percentage to the amount of transfer revenue. The results are fairly even in the four quadrants. In Quadrant II there are 58 villages, with poverty percentage > 40 percent and low transfer income. In Quadrant III which means that the poverty level is low then the value of transfer income is also low with the number of villages is 57. The number of villages in quadrant I is 20 villages with high poverty and low transfer income. The villages in quadrant IV are 17 villages. The villages in quadrant IV are villages with high transfer revenue and also high poverty rates. The conclusion of this research is poverty indicator is no longer focused on economy but also concerning structural, institutional, health and government policy aspects. Development planning needs to be done better so that the village budget can be used as much as possible for the welfare and independence of the community. It is important to the villages to allocate more funds to the populist economic development sector.Keywords: Population, Infrastructure, Expenditure, Revenue, PovertyJEL Classification:H72, I38